Analisis Penerimaan Aplikasi Web Engineering Pelayanan Pengaduan Masyarakat Menggunakan Technology Acceptance Model - Suaidah Lathifah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
P2TP2A-LIP is a women's and children's service institution designed to meet information and needs in the fields of education, health, economy, politics, law, protection and prevention of violence against women and children and human trafficking. As one of the public service facilities, P2TP2A has not implemented information technology to provide services, namely management of public complaints, management of information, consulting services, and outreach to the public. The system in P2TP2A previously was still conventional in the process of managing public complaints, so it is necessary to know how much the acceptance of the new information technology-based system in the public and employees at P2TP2A in using web engineering applications so that it can function optimally. This study aims to analyze the acceptance of a public complaint service web engineering application using the TAM approach. In the TAM approach, there are several factors that are assessed, namely the perceived usefulness and perceived ease of use obtained from the results of the questionnaire given to respondents. The results of this study will show the factors that influence acceptance and how the public's acceptance of the web engineering application for public complaint services at P2TP2A.